PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN PROFITABILITAS TERHADAP KEBIJAKAN HUTANG Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2011 – 2013 - Riyanti Riyanti; Ifah Lathifah (ADVANCE, 2017)
This research aims to analyze and provide empirical evidence of significant influence of managerial ownership, institutional ownership, and the profitability of the debt policy of the companies listed on the Stock Exchange in 2011-2013 period, with a population of 155 manufacturing companies. The sample in this study were obtained by using purposive sampling method. Based on the criteria that is then acquired 33 companies. Analysis of data using multiple regression analysis. The test results indicate that managerial ownership and significant negative effect on the debt policy, institutional ownership has a significant negative effect on the debt policy, and profitability significantly and negatively related to debt policy. This indicates that these three variables is an important element to consider in addressing the agency conflicts that occur in relation manufacturing company in minimizing agency costs. The test results adjusted-R2 of 32.7%, while the remaining 67.3% is explained by other variables outside the model.Keywords: managerial ownership, institutional ownership, profitability and debt policy